CUDA implementation of the antlion optimization algorithm. Issue 2 (4th March 2023) - Davendra, Donald; Metlicka, Magdalena; Bialic-Davendra, Magdalena
Abstract : A parallel version of Ant Lion Optimizer algorithm using the CUDA platform is introduced in this paper. Efficient kernel, memory and thread management approaches have been developed to maximize its performance. The new algorithm was tested against the canonical algorithm on 15 scalable problems of different sizes, with a total of 172 experiments. The solution costs and the execution times were compared using relative percentage difference and significance tests. The results showed the CUDA antlion algorithm significantly improves upon the execution time, while retaining the same solution quality.